ANATOMICAL STRUCTURE OF THE ADRENAL GLAND: A FORENSIC APPROACH - Rayimberdiyev S. (Central Asian Journal of Medicine, 2025)
This article provides a systematic analysis of the anatomical and morphological features of the adrenal glands, which are of significant importance in forensic medical practice. The adrenal glands play a crucial role in maintaining the body’s homeostasis, forming responses to stress, and regulating vital metabolic processes. The article examines their location, external and internal anatomical structure, blood supply, venous drainage, lymphatic flow, and neural innervation. Furthermore, the functional connections of the adrenal glands with the central nervous system and other endocrine organs are highlighted. Particular attention is given to the diagnostic relevance of assessing the condition of the adrenal glands in forensic examinations, identifying their anatomical and topographic changes, and differentiating pathological conditions. These findings serve as an essential scientific and practical basis for in-depth forensic analysis, determining the causes of violent death, and understanding pathologies of the endocrine system.